KOMUNIKASI PEREMPUAN TENTANG HARMONISASI KELUARGA POLIGAMI - Dian Ismi Islami (Jurnal Pustaka Komunikasi, 2022)
Polygamy in Indonesia is legalized in accordance with UUUP No. 1 of 1974 article 3 paragraph (2), while in Islam the Koran allows polygamy contained in the letter an Nisa paragraph 3 but in practice Polygamy causes controversy on people's attitudes in Indonesia, polygamy also has a significant impact in family communication. Women or wives have an important role in realizing polygamous household harmony. Women's communication style is determined by the feelings and quality of the relationship. It is this woman's communication style that determines the harmony of a polygamous family. The problem in this study is how women communicate about the harmonization of polygamous families and what are the barriers to women's communication in polygamous families. This study uses a constructivist paradigm with a descriptive qualitative research type. Data collection by in-depth interviews, observation, the informants in this study were Muslim women in polygamous families.The results of this study indicate that communication between wives in polygamous families is influenced by feelings, closeness or intensity of meetings, and the adjustment process. Meanwhile, communication barriers in polygamous families can occur because of the husband.